(untitled) (Revista do Centro de Estudos Portugueses, 2000)
A obra poética de Carlos Drummond de Andrade apresenta um momento que se afigura diferente dos demais - anteriores e posteriores. É o livro Claro enigma, que contém poemas compostos entre 1948 e 1951. A primeira parte do livro, “Entre lobo e cão”, vai constituir o objeto principal de investigação da poesia pura drummondiana neste artigo. Chamamos essa poesia de pura no sentido de que ela não pretende ensinar, nem emocionar, nem informar nada. É pura no sentido de produzir um certo hermetismo essencial, provocado inicialmente pela própria negação da imagem habitual do mundo e do desejo de depuração verbal. Tende, enfim, à pureza essa poesia que constitui outro mundo, independente, completo, autônomo. Ser outra forma de vida não pressupõe que a poesia exija, para que compartilhemos de seu mundo, uma ruptura total e irreversível com o mundo real, embora demande um tipo diferente de experiência, provocado pela imaginação contemplativa. Carlos Drummond de Andrade’s poetic work presents a moment that appears different from the others - earlier or later ones. It is the book Claro enigma, which includes poems composed between 1948 and 1951. The first part of the work, ”Entre lobo e cão”, is the main object of investigation about Drummond’s pure poetry in this essay. We call this poetry pure in the sense that it doesn’t intend neither to teach, nor to make emotions rise, nor to report facts. It is pure in the sense that it shows a kind of essential hermetical nature, caused initially by the very denying of the habitual image of the exterior world and by the desire of language depuration. In short, this poetry that creates an independent, complete and autonomous world tends towards purity. To be another kind of life doesn’t mean that this poetry requires, for us to share its world, a total and irreversible breaking with the real world, although it demands a different kind of experience, brought about by contemplative imagination.